What are the working mechanisms of a web-based workplace sitting intervention targeting psychosocial factors and action planning? - Katrien De Cocker; Ilse De Bourdeaudhuij; Greet Cardon; Corneel Vandelanotte (BMC, 2017)
Abstract Background Office workers demonstrate high levels of sitting on workdays. As sitting is positively associated with adverse health risks in adults, a theory-driven web-based computer-tailored intervention to influence workplace sitting, named 'Start to Stand,' was developed. The intervention was found to be effective in reducing self-reported workplace sitting among Flemish employees. The aim of this study was to investigate through which mechanisms the web-based computer-tailored intervention influenced self-reported workplace sitting. Methods Employees (n = 155) participated in a clustered randomised controlled trial and reported socio-demographics (age, gender, education), work-related (hours at work, employment duration), health-related (weight and height, workplace sitting and physical activity) and psychosocial (knowledge, attitudes, self-efficacy, social support, intention regarding (changing) sitting behaviours) variables at baseline and 1-month follow-up. The product-of-coefficients test of MacKinnon based on multiple linear regression analyses was conducted to examine the mediating role of five psychosocial factors (knowledge, attitudes, self-efficacy, social support, intention). The influence of one self-regulation skill (action planning) in the association between the intervention and self-reported workplace sitting time was investigated via moderation analyses. Results The intervention had a positive influence on knowledge (p = 0.040), but none of the psychosocial variables did mediate the intervention effect on self-reported workplace sitting. Action planning was found to be a significant moderator (p < 0.001) as the decrease in self-reported workplace sitting only occurred in the group completing an action plan. Conclusions Future interventions aimed at reducing employees' workplace sitting are suggested to focus on self-regulatory skills and promote action planning when using web-based computer-tailored advice. Trial registration Clinicaltrials.gov NCT02672215 ; (Archived by WebCite at https://clinicaltrials.gov/ct2/show/NCT02672215 ).